A longitudinal examination of factors associated with social support satisfaction among HIV-positive young Black men who have sex with men. Issue 12 (2nd December 2017) - McCullagh, Charlotte; Quinn, Katherine; Voisin, Dexter R.; Schneider, John
ABSTRACT: This study examined the long-term predictors of social support satisfaction among HIV-positive young Black men who have sex with men (YBMSM). Data were collected across three waves between October 2012 and November 2014 as part of the baseline assessment from Project nGage, a preliminary efficacy randomized control study examining the role of social support in improving HIV care among YBMSM. The sample included 92 YBMSM aged 18–29. Major results controlling for age, education and intervention effects indicated that psychological health, social network size, and education at baseline predicted differences in social support satisfaction at Wave 3, with no significant effects based on length of HIV diagnosis. Therefore, interventions that are intended to promote the quality of life for YBMSM and their engagement and retention in HIV care must focus on their psychological health concerns and network size.